Rasionalitas Investor Di Bursa Efek Indonesia Didasarkan Pada Pengaruh Pelaksanaan Corporate Social Responsibility (CSR) Terhadap Harga Saham (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia tahun 2007 – 2011) - Sapto Bayu Aji (EBBANK, 2015)
The aim of research to determine the impact of the implementation of CSR expressed by the release of funds toward the investor reaction in the stock market. This study examines whether the Corporate Social Responsibility (CSR) with some of the control variables have an influence on the company's stock price. This study using data of annual financial report and sustainability report from manufacturing companies listed in Indonesia Stock Exchange from 2007 to 2011. Data were analyzed using Pearson correlation and regression analysis. Results of the study found that CSR have a relationship and a significant positive effect on the company's stock price.